Potential implications of a monosynaptic pathway from mossy cells to adult-born granule cells of the dentate gyrus - Scharfman, Helen E.; Bernstein, Hannah L. (Frontiers in Systems Neuroscience, 2015)
The dentate gyrus (DG) is important to many aspects of hippocampal function, but there are many aspects of the DG that are incompletely understood. One example is the role of mossy cells (MCs), a major DG cell type that is glutamatergic and innervates the primary output cells of the DG, the granule cells (GCs). MCs innervate the GCs as well as local circuit neurons that make GABAergic synapses on GCs, so the net effect of MCs on GCs - and therefore the output of the DG - is unclear. Here we first review fundamental information about MCs and the current hypotheses for their role in the normal DG and in diseases that involve the DG. Then we review previously published data which suggest that MCs are a source of input to a subset of GCs that are born in adulthood (adult-born GCs). In addition, we discuss the evidence that adult-born GCs may support the normal inhibitory 'gate' functions of the DG, where the GCs are a filter or gate for information from the entorhinal cortical input to area CA3. The implications are then discussed in the context of seizures and temporal lobe epilepsy (TLE). In TLE, it has been suggested that the DG inhibitory gate is weak or broken and MC loss leads to insufficient activation of inhibitory neurons, causing hyperexcitability. That idea was called the “dormant basket cell hypothesis.” Recent data suggest that loss of normal adult-born GCs may also cause disinhibition, and seizure susceptibility. Therefore, we propose a reconsideration of the dormant basket cell hypothesis with an intervening adult-born GC between the MC and basket cell and call this hypothesis the “dormant immature granule cell hypothesis.”